Intravenous methylprednisolone versus intravenous immunoglobulin in chronic inflammatory demyelinating polyradiculoneuropathy: a randomized trial - Priyanka V Kashyap; Sunil Jee Bhat (International Journal of Medical Research and Review, 2016)
Introduction: Corticosteroids and Intravenous immunoglobulin (IVIg) are effective as initial treatment in patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), but their long-term use is less defined. We compared the efficacy and tolerability of 6-month therapy of intravenous methylprednisolone (IV MP) versus IVIg.Methods: This trial compared efficacy and tolerability of IVIg (0·5g/kg per day for 4 consecutive days) and IV MP (0·5 g in 250 ml sodium chloride solution per day for 4 consecutive days) given every month for 6 months were assessed. After therapy discontinuation, patients were followed up for 6 months to assess relapses.Results: 40 patients (20 IV MP, 20 IVIg) completed the study. More patients stopped MP (12 [60%] of 20) than IVIg (8 [40%] of 20; relative risk 0·54, 95% CI 0·34–0·87; p=0·0085). When adjusted for sex, age, disease duration, comorbidity, modified Rankin scale (mRS) at enrolment, and previous treatment with IVIg and steroids, the difference between the two groups remained significant (odds ratio 7·6, 95% CI 1·7–33·8; p=0·0070). Reasons for discontinuation were lack of efficacy (twelve in the IV MP group vs. 8 in the IVIg group), adverse events (one in the IV MP group), or voluntary withdrawal (2 in IV MP group). The proportion of patients with adverse events did not differ between IV MP group (14 [67%] of 20) and IVIg group (11 [46%] of 20; p=0·1606). After discontinuation, more patients on IVIg worsened and required further therapy (eight [38%] of 20, p=0·0316).Conclusion: Treatment of CIDP with IVIg for 6 months was less frequently discontinued than with IV MP.